NORTH SUMATRA PROVINCIAL GOVERNMENT'S POLICY IN FACING THE COVID-19 PANDEMIC: MAINTAINING THE BALANCE BETWEEN HEALTH AND ECONOMY - Aribowo, Sudiyatmiko; Amin, Muryanto; Subhilhar, Subhilhar; Kusmanto, Heri (International Conference On Social Science Education, 2024)
The COVID-19 pandemic has challenged many governments in managing public health and maintaining economic stability. This study explores the policies implemented by the North Sumatra Provincial Government in balancing public safety and economic interests during the pandemic response in the 2020-2022 period. They are using qualitative research methods with a descriptive approach. The research was conducted in various related institutions, such as BNPB, IDI, and the North Sumatra Provincial Health Office. The results showed that the government implemented various strategic measures, including improving health infrastructure and vaccination programs and supporting MSMEs for economic recovery. This research emphasizes how vital synergy between institutions is to create responsive and adaptive policies in dealing with crises while maintaining economic growth. The North Sumatra Provincial government's policies in dealing with the COVID-19 pandemic show that the government has successfully implemented strategic and comprehensive measures to maintain a balance between health and economy. Focusing on improving health infrastructure, vaccine distribution, and supporting MSMEs through financing and training programs reflects integrated economic recovery efforts. The synergy between the central government, regions, and communities is the key to overcoming the pandemic's impact and building a foundation for sustainable economic growth.